Upaya Penurunan Tingkat Kecacatan Produk dengan Metode DMAIC di PT. X - Sunjono, Amelia Agnes; Halim, Siana (Jurnal Titra, 2015)
This research aims to discover the factors that influences and causes any defects on hollow products of PT. X. We applied DMAIC method to solve the problems. Pareto Chart and Fishbone are utilized for prioritizing and Fishbone discovering the root of the problem, consecutively. As the results, the recommendations that can be given are standardization on some processes such as patri, cukit, and drying, periodical cleaning and maintanance on the machines, calibration on the micrometer, utilizing box for storing the goods, and provide a specific training for the operators in the rangkai and patri departments.